Towards understanding bold behaviour of large carnivores: the case of brown bears in human‐modified landscapes. (27th March 2021) - Bombieri, G.; Penteriani, V; Delgado, M. del Mar; Groff, C.; Pedrotti, L.; Jerina, K.
Abstract: Human–wildlife conflicts sometimes involve bold animals that do not fear humans and their activities. Such behaviour is detrimental to both wildlife and people and may lead to conflicts, which can be especially serious for large carnivores. Like most wildlife, these species have adapted to live in highly humanized landscapes by adopting human avoidance behaviours. However, bold individuals exist, which represent a main cause of conflicts, public fear and negative attitudes, that greatly influence management and conservation actions. Although costly decisions are constantly made to deal with such individuals, evidence‐based knowledge of their behaviour, that is how and when they move, especially in relation to human activities, is lacking. We analysed telemetry data of brown bears ( Ursus arctos ) that were GPS‐collared across Slovenia and Trentino (Italy) to explore spatial behaviour and rhythms of activity of bears that were identified as bold by managers and to assess if and how their behaviour differs from that of their 'non‐bold' conspecifics (hereafter, control individuals). Because other factors such as sex and age of the bear, season, daytime and region may affect behaviour, we also included these variables in our analyses. On one hand, bold bears were more active at the daytime and used open areas considerably more often than control bears. On the other hand, although differences in distance to settlements and roads, movement rates and daily home ranges were also found, they were not as pronounced as expected. Instead, other factors were found to affect bear behaviour and, most importantly, we found strong inter‐individual differences in all behaviours. Such results suggest that, although bold bears have some behavioural attributes in common that distinguish them from control bears, each individual differs from one another. Our study represents a first step towards understanding bold bears' behaviour and provide novel evidence‐based knowledge that can help to better know and manage these individuals. Abstract : Bold bears represent a major cause of conflicts, public fear and negative attitudes towards bears, which greatly influence their management and conservation actions. Although costly decisions are constantly made to deal with such individuals, evidence‐based knowledge of their spatial behaviour, especially in relation to human activities, is lacking. We analysed telemetry data of brown bears ( Ursus arctos ) across Slovenia and the Italian Alps to explore the spatial behaviour and rhythms of activity of bears that were identified as bold by managers and to assess if and how their behaviour differs from that of their "non‐bold" conspecifics. We found that bold bears were more active at daytime and used open areas considerably more often than "non‐bold" bears. However, although differences in other movement parameters were also highlighted, they were not as pronounced as expected. Other factors were found to affect bear movements and, most importantly, we found strong inter‐individual differences in all behaviours. Photo credit: Vincenzo Penteriani